Barcode Reveals Hidden Diversity and Cryptic Speciation among Butterfly Rays Distributed in the Americas - Ehemann, Nicolás Roberto; Siccha-Ramirez, Raquel; Miranda-Romero, Junior; García-Rodríguez, Francisco Javier; De La Cruz-Agüero, José (Taxonomy (Basel, Switzerland), 2024)
The taxonomic status of butterfly rays within the genus Gymnura remains a subject of ongoing debate among researchers. Some authors recognize up to five valid species for the Americas, while others considered several to be synonyms, which has posed a persistent challenge. We aimed to shed light on this complexity by employing molecular operational taxonomic units (MOTUs) based on the mitochondrial gene cytochrome oxidase I (COI). Genetic sequences were obtained from fresh muscle tissue collected in the marine ecoregions corresponding to the type locality from all the nominal butterfly ray species distributed along the Eastern Tropical Pacific (ETP). Our results unveiled compelling findings; all the species delimitation models used consistently identified seven MOTUs for the American continent and an extra G. altavela MOTU restricted to Africa. In addition, our results and models exceeded the worldwide accepted interspecific threshold of 2.0%. Remarkably, our results support the taxonomic reinstatement of Gymnura afuerae (Hildebrand, 1946) as a valid species, with a range expanding into the ETP in the Southern Hemisphere. Similarly, our data support the recent suggestion of resurrecting Gymnura valenciennii (Duméril, 1865) as a valid species in the western Atlantic. These findings urge a reassessment of the conservation status and a comprehensive taxonomic revision of American butterfly rays.